Familial intestinal degenerative neuropathy with chronic intestinal pseudo-obstruction linked to a gene locus with duplication in chromosome 9. (2nd December 2019) - Abrahamsson, Hasse; Ahlfors, Frida; Fransson, Susanne; Nilsson, Staffan; Linander, Hans; Martinsson, Tommy
Abstract: Background: Intestinal degenerative neuropathy without extra-intestinal involvement occurs as familial forms (FIDN) but the genetics behind is unknown. We studied a Swedish family with autosomal dominant disease and several cases of chronic intestinal pseudo-obstruction (CIP). Methods: We included 33 members of a family sharing a male ancestor. Chronic intestinal symptoms including diarrhoea occurred in 11, four had severe CIP. DNA was analysed with SNP-microarray (Affymetrix), linkage (Allegro Software) and gene dosage (CNAG 3.0). Results: Genetic linkage was found to the short arm of Ch9 to a 9.7 Mb region with 45 protein-coding genes, 22 of which were duplicated (1.2 Mb duplication) (dup(9)(p21.3) with breaking point in the FOCAD -gene. Lod score for the region was 3.4. Fourteen subjects were duplication carriers including all 11 subjects having severe chronic symptoms/CIP. Nineteen subjects had no duplication. The occurrence of gastrointestinal symptoms in the family was strongly linked to duplication carrier-ship ( p  = .0005). The two branches of the family had separate maternal ancestors (A and B). Including the previous generation, severe disease (overt CIP and/or death from intestinal failure) was assessed to occur in 100% (5/5) of duplication carriers in branch A and in 21% (3/14) in branch B ( p  = .005). In branch B the onset of symptoms was later (median 38 vs. 24 yrs) and three duplication carriers were symptom-free. Conclusions: In this family with autosomal dominant hereditary intestinal neuropathy, the disorder is linked to a 9.7 Mb region in Ch9 including a 1.2 Mb duplication. There is a significant difference in disease expressivity between family branches, seemingly related to separate maternal ancestors.